Antiarrhythmic Drug Therapy in Cardiomyopathies: A Comparative Synthesis of Guidelines and Consensus Documents - Andrea Palermi; Massimo Di Marco; Silvio Saraullo; Roberta Magnano; Laura Pezzi; Davide Rossi; Giulia Renda; Sabina Gallina; Gianfranco Sinagra; Marco Merlo (Current Cardiology Reports, 2026)
Abstract Purpose of Review Antiarrhythmic drug therapy in cardiomyopathies remains challenging because arrhythmic risk, drug efficacy, and pro-arrhythmic vulnerability vary substantially across phenotypes. This review summarizes contemporary guideline and consensus recommendations on antiarrhythmic drug use in hypertrophic, dilated, non-dilated left ventricular, and arrhythmogenic cardiomyopathies. Recent Findings Recent guidelines increasingly emphasize phenotype-oriented arrhythmia management, but specific recommendations for antiarrhythmic drug therapy remain fragmented. Beta-blockers and amiodarone are the most consistently recommended agents in structural heart disease, whereas class I drugs are generally restricted. Evidence is strongest for hypertrophic and arrhythmogenic cardiomyopathies, while recommendations for dilated and non-dilated left ventricular cardiomyopathies are largely extrapolated from broader heart failure populations. Summary Antiarrhythmic drugs are mainly used to reduce arrhythmic burden, symptoms, and implantable cardioverter-defibrillator therapies rather than to improve survival. Future studies should define phenotype-specific strategies based on ventricular function, myocardial scar, genotype, and clinical context.